Heck reactions of aryl halides with styrene using 1-butyl-3-methylimidazolium bromide ionic liquid as a green solvent under microwave irradiation - Son Nam, Phan Thanh; Hoai An, Nguyen Thi; Ngoc Diem, Le Thi (Vietnam Journal of Chemistry, 2014)
Easily accessible ionic liquids, 1-butyl-3-methylimidazolium bromide, 1-hexyl-3-methylimidazolium bromide, and 1-octyl-3-methylimidazolium bromide, respectively, were synthesized under microwave irradiation condition, and characterized by 1H and 13C NMR, and MS. The three ionic liquids were demonstrated to be an efficient and recyclable solvent for the Heck cross-coupling reaction between several aryl halides and styrene under microwave irradiation to form trans-stilbenes as the principal products. Interestingly, it was found that increasing the length of the alkyl chain in the ionic liquid caused a significant drop in the reaction rate. Higher reaction rate was observed for the Heck reaction using 1-butyl-3-methylimidazolium bromide, as compared to that of the reaction using 1-hexyl-3-methylimidazolium bromide, and 1-octyl-3-methylimidazolium bromide, respectively. Using the ionic liquid as the reaction solvent in conjunction with microwave irradiation, the reaction rate was dramatically enhanced, with 99% conversion being achieved within 1.5 minutes for the butyl-based ionic liquid, compared to conversions obtained after 2 hours under conventional conditions. Furthermore, the ionic liquid – Pd2+ system could be reused in subsequent reaction without significant degradation in activity.